2003
DOI: 10.1073/pnas.1833106100
|View full text |Cite
|
Sign up to set email alerts
|

Low monoamine oxidase B in peripheral organs in smokers

Abstract: One of the major mechanisms for terminating the actions of catecholamines and vasoactive dietary amines is oxidation by monoamine oxidase (MAO). Smokers have been shown to have reduced levels of brain MAO, leading to speculation that MAO inhibition by tobacco smoke may underlie some of the behavioral and epidemiological features of smoking. Because smoking exposes peripheral organs as well as the brain to MAO-inhibitory compounds, we questioned whether smokers would also have reduced MAO levels in peripheral o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
1
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 41 publications
2
57
1
2
Order By: Relevance
“…Additionally, a human post-mortem study of chronic smokers demonstrated a modest reduction in MAO A binding that did not reach statistical significance (Klimek et al, 2001). Peripheral MAO B is also reduced in cigarette smokers (Fowler et al, 2003b).…”
Section: Monoamine Oxidase Function In Smokersmentioning
confidence: 99%
“…Additionally, a human post-mortem study of chronic smokers demonstrated a modest reduction in MAO A binding that did not reach statistical significance (Klimek et al, 2001). Peripheral MAO B is also reduced in cigarette smokers (Fowler et al, 2003b).…”
Section: Monoamine Oxidase Function In Smokersmentioning
confidence: 99%
“…In addition, trans,trans-farnesol, a component of tobacco smoke, is a potent, reversible inhibitor specific for MAO B. 2 Another study has established that 1,4-diphenyl-2-butene (K i ϭ 35 M), a contaminant of polystyrene bridges used for MAO B crystallization, and 1,4-diphenyl-1,3-butadiene (K i ϭ 7 M) are potent, competitive MAO B-specific reversible inhibitors (6,7). Because none of these compounds (see Scheme 1 for their respective structures) inhibit MAO A, a more detailed study of the molecular basis for their specificities could provide opportunities to develop MAO B-selective inhibitors with potential neuroprotective properties.…”
mentioning
confidence: 99%
“…The interesting question is whether any of these also contributes to the reinforcing properties of tobacco smoke. It has been known for some time that cigarette smoke inhibits monoamine oxidase (MAO), the enzyme that catalyses the metabolism of monoamine neurotransmitters, such as dopamine, thus potentiating their effects in the brain of smokers and thereby contributing significantly to reward and dependence (Fowler et al, 2003). Nicotine is not directly responsible for this effect (Fowler et al, 1999).…”
Section: Dependence To Tobacco Is It All About Nicotine?mentioning
confidence: 99%